2017
DOI: 10.1111/aji.12622
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal peritoneal regulation of chemokine activation—The role of IL‐8 in pathogenesis of endometriosis

Abstract: It may act as an autocrine growth factor in the endometrium and promotes the vicious circle of endometrial cell attachment and, in consequence, may lead to a transformation from acute to chronic inflammation stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 71 publications
4
61
0
3
Order By: Relevance
“…2F). Although ROS levels were not measured in this particular arm of our study, this observation suggests a potential pathophysiological mechanism in endometriosis, and in general confirms the previous observation of elevated IL-8 levels in endometriosis 31 .…”
Section: The Lipid Peroxidation Product 4-hne Is Present In Ectopic Lsupporting
confidence: 91%
See 1 more Smart Citation
“…2F). Although ROS levels were not measured in this particular arm of our study, this observation suggests a potential pathophysiological mechanism in endometriosis, and in general confirms the previous observation of elevated IL-8 levels in endometriosis 31 .…”
Section: The Lipid Peroxidation Product 4-hne Is Present In Ectopic Lsupporting
confidence: 91%
“…The angiogenic properties of this chemokine have long been recognized, particularly in oncology 45 , and also in endometriosis 46 . The clinical data from us and others that IL-8 is significantly elevated in the PF of women with endometriosis 31 and associated with pain 47 , further supports the observation that this cytokine promotes the disease in a dose-dependent manner 48,49 .…”
Section: Discussionsupporting
confidence: 66%
“…Angiogenesis plays an essential role in the growth and survival of endometriotic lesions . Previously, we and others demonstrated that ERK1/2 signaling contributes to growth of endometriotic lesions by enhancing proliferation of endometriotic stromal cells .…”
Section: Introductionmentioning
confidence: 80%
“…However, the most accepted etiological theory is retrograde menstruation, which enables recruitment of viable endometrial tissues into ectopic sites such as the peritoneal cavity with subsequent cellular attachment to peritoneal surfaces, implantation, and neovascularization prompting endometriotic tissue growth . Previous studies demonstrated elevated peritoneal levels of pro‐inflammatory chemokines monocyte chemo‐attractant protein (MCP)‐1, Interleukin (IL)‐8, fractalkine, and increased inflammatory cell recruitment, and/or elevated levels of IL‐6 and prostaglandins associated with pelvic pain in women with endometriosis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation